2021
DOI: 10.2991/assehr.k.210427.048
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Technology to Promote Learner Autonomy in Teaching English

Abstract: This study aimed at investigating EFL teachers' perceptions of the use of technology to promote learner autonomy in teaching English. A focus group research was used as its design with qualitative analysis for data interpretation. The participants of the study were five English teachers who teach English as a foreign language in Indonesia. The data were collected from an online discussion forum and analysed through data reduction, data display for categorization, and conclusion. The study reveals that EFL teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…The problem includes inadequate internet access in schools and misuse of handphones by students for things that are not related to the teaching and learning process such as viewing social media. This finding is almost the same as the results of research from Melvina et al, (2021) that from the data obtained from the interview results it was reported that teachers had problems using technology in the process of teaching and learning English in class. The main problem found is the limited internet connection.…”
Section: Resultssupporting
confidence: 88%
“…The problem includes inadequate internet access in schools and misuse of handphones by students for things that are not related to the teaching and learning process such as viewing social media. This finding is almost the same as the results of research from Melvina et al, (2021) that from the data obtained from the interview results it was reported that teachers had problems using technology in the process of teaching and learning English in class. The main problem found is the limited internet connection.…”
Section: Resultssupporting
confidence: 88%
“…Cotton et al [ 25 ] also highlighted that the rise of these CAI tools could bring about dishonesty among students' academic work such as plagiarism and cheating. Contrary, the study of Melvina et al [ 26 ] presented that other faculty members have seen the benefit of using these CAIs as an educational tool – establishing technology adoption for both students and teachers. Benichou [ 27 ] also expressed the heightened utility of CAIs on educational work attainment among students since the development of these applications brought guidance, support, and/or development on students' schoolwork and related tasks.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, technology nowadays plays a significant role in our lives (Ottenbreit-Leftwich et al, 2010). Media technology is most likely one of the impacts of technology in education as a medium for students to improve their learning (Li et al, 2019;Melvina et al, 2021). Menggo et al proved that many speaking classes have extensively applied multi-media technology to practice speaking inside as well as outside the English classroom realm (Menggo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%